Assessment of Morbidity Patterns and Occupational Hazards Among Food Handlers in Food Establishments in Tamilnadu, India - Priyadharshini P; M Logaraj; VV Anantharaman (National Journal of Community Medicine, 2024)
Background: Rapid urbanization has increased the intake of external (outside) foods, causing a surge in food-borne diseases. In the South-East Asian region of the World Health Organization, 150 million people fall ill with foodborne diseases every year, of which, 1.75 lakhs perish. Occupational hazards are of public health importance as they cause permanent disability, loss of livelihood, and morbidity. Methodology: This cross-sectional study was conducted among 235 food handlers working in food establishments of a private educational institution in Tamil Nadu using a semi-structured pre-tested questionnaire. Descriptive statistics, odds ratio and one-way ANOVA were used. Occupational risk score was calculated. Data were analyzed using SPSS 22.0. Results: The mean age of the food handlers was 30.7 (SD=10.3). Of the 235 participants, the majority were Males (86%). The commonest acute morbidity was Acid peptic disease (48.5%). Hypertension was reported in 26% of subjects. The most common occupational hazard was prickly heat (74.9% of the subjects). Work-related stress was reported by 72% of the food handlers. Physical hazards were high with a Mean value of 11.67 (SD=5.9) Conclusion: Half the subjects reported Acid Peptic Disease as the most common morbidity. Burns at work and psycho-social issues were found at higher rates. Periodic deworming, vaccination against enteric organisms, routine examinations and ergonomically designed workplaces can prevent outbreaks and preserve workers’ health.